Аналіз судової практики стосовно звільнення особи від кримінальної відповідальності за декларування недостовірної інформації (стаття 3661 Кримінального кодексу України) - Загиней, З.; Zahynei, Z. (Волин. нац. ун-т ім. Лесі Українки, 2018)
У статті проаналізовано судову практику в частині звільнення осіб від кримінальної відповідальності за декларування недостовірної інформації (стаття 3661 Кримінального кодексу України). Зроблено висновок про хибність підходу практичних працівників, які вбачають у поданні суб’єктом декларування електронної декларації шляхом заповнення на офіційному веб-сайті Національного агентства з питань запобігання корупції, після попередження, зробленого цим агентством, зміну обстановки як підставу для звільнення особи від кримінальної відповідальності. The article analyzes the judicial practice in terms of exempting individuals from criminal responsibility for declaring inaccurate information (Article 3661 of the Criminal Code of Ukraine). It was concluded that practitioners' approach is incorrect, who see the submission of an electronic declaration as a subject by declaring an electronic declaration on the official website of the National Agency for the Prevention of Corruption, after the warning made by this agency, a change of situation as a basis for exempting a person from criminal liability. Filling a declaration with an electronic declaration by the subject does not indicate a certain change in the situation, since its presentation does not indicate a change in the external conditions, but an internal incentive for the guilty to fulfill his duty as provided for in the anticorruption legislation of Ukraine. The most likely in this situation is the decision to release the person from criminal responsibility in connection with active repentance. However, this decision may be refutable, since in the case when the declaration of the subject of declaration is placed on the official website of the National Agency for the Prevention of Corruption in the Unified State Register of persons authorized to perform the functions of the state or local government, this may indicate the absence of such an element crime, as its subjective side.
Analysis of Judicial Practice Regarding the Rlease of a Person from Criminal Responsibility for the Declaration of Inaccurate Information (Article 366-1 of the Criminal Code of Ukraine)
Keywords: декларування недостовірної інформації; електронна декларація; особа; уповноважена на виконання функцій держави або місцевого самоврядування; фінансовий контроль; звільнення від кримінальної відповідальності; зміна обстановки; дійове каяття; declaration of false information; electronic declaration; person authorized to perform functions of the state or local self-government; financial control; release from criminal responsibility; change of situation; effective repentance